P3.39 Molecular detection of trichomonas vaginalis virus in direct trichomonas vaginalis positive clinical samples from the netherlands. (8th July 2017) - Veer, C Van der; Jehee, I; Himschoot, M; Hermans, M; Bruisten, S
Abstract : Introduction: Two genotypes are described for Trichomonas vaginalis (TV). TV genotype I seems to be more susceptible to metronidazole, but also more prone to TV virus (TVV) infection, than type II. The release of TVV during treatment may in itself be pathogenic. Four TVV genotypes have been described, but epidemiological studies are rare as culturing TV ahead of TVV detection is laborious. We therefore developed a sensitive method to detect and type TVV in TV positive clinical samples directly. Methods: TV positive samples (by NAAT) were collected from two Public Health Laboratories in the Netherlands, from 2012 to 2016. TV was typed using multi-locus sequence typing (MLST) of 7 household genes. MLST profiles were put into a minimum spanning tree together with reference strains and so allocated a genotype. TVV RNA was detected using nested reverse-transcriptase PCR with newly designed primers and visualised on gel. Results: We included 157 clinical samples from 151 clients (most were female; n=133, 87%). In total, 120 samples were genotyped for TV; TV genotype I was most common (n=65;54%). Over half of these samples were found positive for TVV RNA (n=65; 54%). Most TVV infections were found in TV genotype I (n=49; 75%). The amplified products for TVV1, TVV2 and TVV3 were respectively 97 bp, 290 bp and 156 bp and sequencing showed high identity with TVV genomes; TVV1-C344 (93%), TVV2-OC3 (89%) and TVV3-UR1 (85%), supporting specificity of the primers for these targets. TVV1 was most prevalent (n=45; 41%), followed by TVV3 (n=34;31%) and finally TVV2 (n=31; 28%). Co-infections occurred in 60% of TVV positive samples. TVV4 was not found at all. Sensitivity for TVV detection still needs to be established using TV samples with a known TVV (genotype) status. Conclusion: TVV detection can be performed directly on clinical samples using nested RT-PCR. TVV infection occurs most frequently in TV type I parasites as in agreement with previous findings. This opens the way for molecular epidemiological studies to gain insight into the role of TVV in TV pathogenicity.